Stewards of the nation's art : contested cultural authority, 1890-1939 - Geddes Poole, Andrea, 1959- (Book collections on Project MUSE., 2010)
Stewards of the Nation's Art examines the internal tensions between Britain's four main public art galleries' administrative directors, the aristocrats dominating the boards of trustees, and those in the Treasury who controlled the funds as well as board appointments.